Design and Kinematic Simulation of the Transposition Mechanism of Wheelchair-hand Control System - Pan Liping; Ge Fei; Su Daoquan; Wan Chaoyan (Jixie chuandong, 2015)
With the help of Auto CAD,the transposition linkage mechanism of wheelchair-hand control system used for the elderly and disabled is designed by using graphical method.The mathematic model of the mechanism is built,the correctness of the design result is verified by using the analytical method.The mathematic model of the mechanism is built in ADAMS,and the kinematics simulation is carried out,the various positions of the requirement of the transposition linkage mechanism of wheelchair-hand control system are obtained.It is shows that the mechanism meet the challenge of motion continuity and without malposition and re-ordering problem,the useful reference for verifying the feasibility and rationality of design scheme is provided.